Research on a coupler with arc surface contact and its effect on a train collision. (April 2023) - Zhou, Hechao; Wang, Xupeng; Wang, Yuwei; Zhan, Jun; Zhang, Jimin
Based on the multi-body dynamics a three-dimensional train collision model including a coupler-buffer substructure is established in this paper. During the train collision, the dynamic responses of coupler-buffer substructure are comprehensively analysed. Some key parameters, such as the coupler initial deflection angle, max-angle, friction force at the arc contact surface and buffer impedance force, are investigated and their effects on the train derailment are also evaluated. The simulation results indicate that during a train collision the longitudinal impact force is so large that the coupler-buffer device reveals a weak ability to anti-jackknifing. As a result, in some cases the coupler rotation angle is very large and equal to its designed max-angle. Under the effect of this large coupler rotation angle, the collided trains have a risk to derail. In order to improve the collided train's safety against derailment, a high friction force at the coupler arc contact surface and a low coupler max-angle are suggested.